2011
DOI: 10.1186/1471-2474-12-91
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ultrasound and clinical examination in the detection of flexor tenosynovitis in early arthritis

Abstract: BackgroundTenosynovitis is widely accepted to be common in rheumatoid arthritis (RA) and postulated to be the first manifestation of RA, but its true prevalence in early disease and in particular the hand has not been firmly established. The aims of this study were first to investigate the frequency and distribution of finger flexor tenosynovitis using ultrasound in early arthritis, second to compare clinical examination with ultrasound (US) using the latter as the gold standard.Methods33 consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
3
28
2
1
Order By: Relevance
“…This incidence was much higher than was reported in other cohorts in the literature [25][26][27], which indicated the presence of tenosynovitis in approximately 50-60 % of included patients. In a group of 50 patients with early, untreated RA, Wakefield et al [36] found flexor tenosynovitis in 82% of patients with MRI and in only 48% of patients with US.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This incidence was much higher than was reported in other cohorts in the literature [25][26][27], which indicated the presence of tenosynovitis in approximately 50-60 % of included patients. In a group of 50 patients with early, untreated RA, Wakefield et al [36] found flexor tenosynovitis in 82% of patients with MRI and in only 48% of patients with US.…”
Section: Discussioncontrasting
confidence: 51%
“…Some studies regarding US incidence [25][26][27], validity [13] and inter-observer reliability of US detection of tenosynovitis involving multiple investigators [28][29][30][31] have been performed. Tenosynovitis has been included together with synovitis without separation between joints and tendons' pathology in some described US scores [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Tenosynovitis is common in RA [Hmamouchi et al 2011] but its true prevalence in early disease has not been firmly established. A complication of persistent tenosynovitis is complete rupture of the tendon with loss of function [Mcqueen et al 2005].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Musculoskeletal ultrasound (MSUS) has already proven its utility for directly visualization of the joint synovial tissue (morphology and quantification), the synovial vascularization (presence and quantification), and in monitoring the response to therapy [18][19][20][21][22][23][24][25][26][27]. Recently, much attention has been given to the presence of tenosynovitis, as a constant, complementary, but different facet of the inflammatory involvement in RA [28][29][30]. In this scenario, identification of tenosynovitis in early RA stages along with treatment monitoring in early and established disease should not only help in improving the new classification criteria but also in preventing or slowing down the development of structural damage at tendon and joint level [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%